Evaluation and standardisation of different matrices used for double-blind placebo-controlled food challenges to fish - Vassilopoulou, E.; Douladiris, N.; Sakellariou, A.; Cortes, S. V.; Sinaniotis, A.; Rivas, M. F.; Papadopoulos, N. G. (J Hum Nutr Diet, 2010)
Fish allergens represent one of the most common causes of adverse reactions to food worldwide. Double-blind placebo-controlled food challenges (DBPCFC) are the gold standard for food allergy diagnosis. However, no standardised recipes are available for common food allergens such as fish, and a well trained dietitian is essential for creating and standardising them. The present study aimed to create and standardise recipes for use in DBPCFCs to fish.|Three recipes were prepared. Employing a standardised procedure, a total of 35 panelists evaluated the different matrices using an evaluation form. A paired comparison test was used to estimate total evaluation's outcome. Fish allergic patients were challenged with different fish species blinded with the selected matrix and evaluated the recipe using the same form.|From a base recipe and step-by-step modifications, a low fat recipe was selected among other recipes tested, which proved to be appropriate for fish blinding, in terms of taste, odour, appearance and blinding. Patients challenged with the final matrix found it acceptable, no matter which fish type was used.|In this pilot study, a recipe with satisfactory organoleptic characteristics was developed and validated for DBPCFC to fish.
Keywords: Adult Allergens Animals Child Cookbooks as Topic Diagnostic Techniques and Procedures Dietary Fats Dose-Response Relationship; Immunologic Double-Blind Method Female Fish Proteins Fishes Food Hypersensitivity Humans Immunoglobulin E Male Seafood Sensation Skin Tests Young Adult